If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32 = 3t + 14 Reorder the terms: 32 = 14 + 3t Solving 32 = 14 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. 32 + -3t = 14 + 3t + -3t Combine like terms: 3t + -3t = 0 32 + -3t = 14 + 0 32 + -3t = 14 Add '-32' to each side of the equation. 32 + -32 + -3t = 14 + -32 Combine like terms: 32 + -32 = 0 0 + -3t = 14 + -32 -3t = 14 + -32 Combine like terms: 14 + -32 = -18 -3t = -18 Divide each side by '-3'. t = 6 Simplifying t = 6
| 5x+-4=51 | | p*x=34 | | 5a+9=-16 | | px=34 | | 4n+9=53 | | 139-4x=6x+97 | | -47-2x+9=10x | | 2y-3=5y-4y | | 1-3y+2/3y=2 | | 7x-14=-7x+42 | | 4x^3-20x^2-x+5=0 | | 4x+38=7+11 | | n=xp | | 2/3n-1/2n | | a-h=m | | a+h=mforh | | a+h=m | | -10=-4+7x | | 2m+3=11(2m+3) | | 6(d-4)+3= | | 11x+5=90 | | -2(x-4)=-3x | | 2+x+x+x+2x+10= | | y^2-6y-55=0 | | 7/12*y | | 5x+3=-6+3x+15 | | (64/125)^-2/3 | | -1=t-7 | | 5k-k-8= | | 0=-6y^2+17y-12 | | 12/x-2=8 | | 3.1(m+9)+3.4m= |